Digital age literacy profile of high school students and its implementation in biology learning - Anik Roslina Rosyadi; Afandi Afandi; Eko Sri Wahyuni (Department of Biology Education, Universitas Pendidikan Indonesia, 2022)
This study aims to describe high school students’ digital-age literacy skills. This study is a descriptive study with a quantitative approach. The sample of this study was 322 eleventh-graders of science at SMA Negeri in Pontianak City, which were determined using the cluster sampling technique. The instrument used is a questionnaire developed based on eight domains of digital-age literacy. The results showed that students' level of digital-age literacy was included in the medium category. Based on the domain, technological literacy, multicultural literacy, and global awareness were in the high category, while basic literacy, information literacy, scientific literacy, visual literacy, and economic literacy were in the medium category. The implementation of digital-age literacy in biology learning is expected to create more engaging and effective biology learning and improve students' digital-age literacy skills.